Self-erasing discharge mode for improvement of luminous efficiency in AC plasma display panel. - Heung-Sik Tae
The current paper proposes a new self-erasing discharge mode to improve the luminous efficiency in an ac plasma display panel (ac-PDP). The self-erasing discharge mode is produced by simultaneous application of auxiliary short pulses to the address electrodes at the falling edges of the sustain pulses. By proper adjusting of the amplitude and width of the auxiliary short pulses, an improved luminous efficiency of 26% and luminance of 9% were simultaneously obtained under the stable driving voltage margin condition (>60 V).
Keywords: 60 V; AC plasma display panel; Address electrode; Auxiliary short pulse; Luminance; Luminous efficiency; Self-erasing discharge mode; Voltage margin